PELANGGARAN PERPRES NOMOR 54 TAHUN 2010 TENTANG PENGADAAN BARANG DAN JASA PEMERINTAH OLEH PENYEDIA BARANG DAN JASA ATAU PENGGUNA JASA DALAM PERSPEKTIF TINDAK PIDANA KORUPSI - Jawade Hafidz; Agung Widodo (Jurnal Pembaharuan Hukum, 2015)
The government as a provider of services to the community, is both basic services and basic semi- service the needs of society. Basic categories of services financed through the taxsystem, while the semi basic services financed through levies which essentially is a community participation in financing certain services in question. The research method using normativejuridical approach that was then analyzed qualitatively normative. The results obtained states that: 1).Implementation of Presidential Decree 54 of 2010 on the procurement of goods and services may not be helpful and not useful. This is because it turns out the implementation activities of government goods/services, violations can occur at anytime in any process. Potential violations in procurement of government goods/serviceshave occurred from the initial stage to the final stage, which can be divided into three phases:preparation, implementation phase, and phase. 2).Countermeasures violations carried out in the form of supervision over the course of Presidential Decree No. 54 of 2010 Concerning Procurement of Government Goods and Services so that they can minimize the potential for evil that can cause irregularities that led to the creation of unfair business competition.